DHX9 : novel roles in cytokine induction and its antagonism by vaccinia virus protein E3 - Dempsey, Alan (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Vaccinia virus (VACV) is a dsDNA virus, which replicates in the cytoplasm of infected host cells. VACV, similar to other viruses, is detected by host innate immunity mainly by sensing of viral nucleic acids such as dsRNA, leading to type I interferon (IFN) and cytokine induction. A major contributor to the ability of VACV to target IFN is the dsRNA-binding protein E3. Mass spectrometry analysis previously identified DEAH-box polypeptide 9 (DHX9) as a novel interacting partner of E3. DHX9, an RNA helicase vital in various aspects of RNA metabolism, had previously been shown to bind to the p65 subunit of NF-κB to enhance NF-κB-dependent gene expression. Recently, DHX9 was proposed as a cytoplasmic nucleic acid sensor in dendritic cells of CpG-B DNA and dsRNA, signalling via MyD88 and MAVS, respectively. The aims of this project were to investigate immune functions of DHX9 and then to determine whether E3 could antagonise these.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin